Inclusivism: Ethical Values of Future Religious Education - Afifuddin Afifuddin; Muhammad Alqadri Burga (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2023)
Religious plurality and social pluralism in Indonesia are like a double-edged sword.  On the one hand, it can strengthen social ties and cooperation between social joints, but on the other hand, it is very vulnerable to conflicts, both inter-religious and inter-religious groups.  This paper describes how diversity also has an impact on educational institutions and the importance of providing moral awareness to students in schools to live side by side, in harmony and peace within the framework of plurality and humanity, especially in facing the social lifestyle in the industrial era 5.0. Inclusiveness is full of values of respect for differences, openness to accepting diversity, upholding humanity above individualistic interests, and a great willingness to blend in and stick together in brotherly bonds that actually should be used as ethical values in religious education in schools.  Thus, the purpose of this paper which is sourced from in-depth social analysis and relevant literature studies is to provide understanding and awareness that religious education in school institutions should move from just formalistic-dogmatic learning to be a substantial learning, egalitarian and educates students to promote moderate, tolerant and inclusive attitudes towards religious diversity and avoid potential social conflicts.  Building inclusivism in schools starts with creating a climate of religious education that is open to all and not divided based on the religion of the students.  Furthermore, religious education puts forward human values and universal goodness to eliminate bad prejudice and hatred towards different communities.